Nanometer material coating capable of resisting fabric surface fuzzing and preparation method of nanometer material coating

Through the synergy between functionalized core-shell nanoparticles, polyionic liquid materials and aqueous polyurethane-acrylic emulsion, nanomaterial coatings that resist bleaching on the surface of fabric are prepared, solving the problem of bleaching on the surface of fabric and achieving efficient bleaching and high comfort.

CN119859922AActive Publication Date: 2025-04-22SHANGHAI RONGHUA INTELLIGENT TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510352471.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-25
Publication Date
2025-04-22
Estimated Expiration
2045-03-25

AI Technical Summary

Technical Problem

The surface of the fabric is prone to bleaching and pilling, which affects the appearance aesthetics and functionality. It is difficult for traditional solutions to meet the requirements of anti-bleaching and high comfort at the same time.

Method used

A nanomaterial coating that resists irrigation on the surface of fabrics is prepared by synergistically acting as functionalized core-shell nanoparticles, polyionic liquid materials and aqueous polyurethane-acrylic emulsion. This coating reduces friction and static accumulation between fibers and reduces fiber entanglement and fracture by forming a uniform and dense protective layer on the fiber surface.

Benefits of technology

Significantly improve the anti-blending performance of fabrics, extend the service life of fabrics, while maintaining high comfort, meeting multiple requirements such as anti-blending and high comfort.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859922A_ABST
    Figure CN119859922A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of nano-material coatings, and provides a nano-material coating capable of resisting fabric surface fuzzing and a preparation method of the nano-material coating. Firstly, a functionalized polysiloxane core is obtained through the synergistic effect of polyhedral oligomeric silsesquioxane and graphene quantum dots, the functionalized polysiloxane core is combined with a polar group on the surface of a fabric fiber through intermolecular interaction to enhance adhesive force, a hydrophobic group reduces the friction coefficient between fibers, meanwhile, electrostatic accumulation is effectively reduced, and the entanglement phenomenon caused by electrostatic attraction is reduced. Secondly, positive ions, carboxyl and other polar groups in the introduced polyion liquid can form a compact protective layer on the surface of the fiber, and are combined with the polar groups on the surface of the fiber through hydrogen bonds or electrostatic interaction, so that the electrostatic attraction at the tail end of the fiber is effectively shielded, and fiber entanglement and hair balls are reduced; in addition, due to the ionic conductivity of the polyion liquid, the anti-static property is achieved, static charges accumulated in the friction process can be rapidly released, and the fluffing phenomenon is further inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano material coating preparation, and relates to a nano material coating capable of resisting fuzzing on the surface of fabric and a preparation method thereof. Background Art

[0002] As the frequency of fabric use increases and the duration of use increases, pilling and other phenomena are prone to occur on the fabric surface, which not only affects the appearance of the fabric, but also reduces its functionality and service life. Especially in the field of high-end clothing and functional fabrics, the pilling problem is particularly prominent. Therefore, how to effectively suppress the pilling phenomenon on the fabric surface has become an important research topic in the textile field. The pilling on the fabric surface is caused by the fiber breaking or falling off under the action of external forces (such as friction, stretching, etc.), and the formation of pilling on the fabric surface. Pilling not only affects the appearance quality of the fabric, but also makes its touch worse. In addition, for some functional fabrics (such as waterproof, anti-fouling or conductive fabrics, etc.), the pilling phenomenon may damage its functional coating, resulting in a significant decrease in performance. Traditional solutions to the problem of fuzzing on the fabric surface mainly include: mechanical treatment, reducing the length of the fibers on the fabric surface by shearing, singeing, etc., thereby reducing the possibility of fuzzing. Although this method is simple and effective, it will cause certain mechanical damage to the fabric and the effect is not long-lasting; by coating resin to enhance the bonding force of the fibers so that the fibers are not easy to slip out of the yarn, this type of method can significantly improve the anti-fuzzing performance of the fabric, but often reduces the fabric's softness, breathability and other comfort indicators. Although the above methods have alleviated the fuzzing problem of fabrics to a certain extent, they also have many limitations and it is difficult to meet multiple requirements such as anti-fuzzing and high comfort at the same time.

[0003] In recent years, with the development of nanotechnology, the application of nanomaterials in the textile field has received more and more attention, mainly due to their unique physical, chemical and mechanical properties. Nanomaterials have extremely small particle size, ultra-high specific surface area and unique surface effect. Compared with traditional materials, they have advantages in improving fabric performance. The high specific surface area of ​​nanomaterials enables them to form a stronger binding force with the fiber surface. After the nanomaterials are coated on the surface of the fabric, the adhesion between the fibers can be enhanced, thereby reducing the phenomenon of fiber slippage due to external forces. It can not only effectively inhibit the fuzzing of the fabric surface, but also extend the service life of the fabric; the good dispersibility and high activity of nanomaterials enable them to be evenly distributed on the fabric surface and form a dense protective layer with the fibers. Therefore, the preparation of a nanomaterial coating that resists fuzzing on the fabric surface has good application prospects. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a nanomaterial coating for preventing the fuzzing of fabric surfaces and a preparation method thereof, which combines the synergistic effect of functionalized core-shell nanoparticles, polyionic liquid materials and aqueous polyurethane-acrylic emulsion to prepare a functional coating with high efficiency in preventing the fuzzing. The coating forms a uniform and dense protective layer on the fiber surface, effectively reduces the friction and static electricity accumulation between fibers, reduces fiber entanglement and breakage, thereby improving the anti-fuzzing performance of the fabric, and thus meeting the needs of actual production.

[0005] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a nano-material coating for preventing fuzzing on a fabric surface, the preparation method comprising: S1, adding a cage-type polysilsesquioxane dispersion into a graphene quantum dot dispersion, adding ammonium persulfate, and reacting to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, adjusting the pH to 9 for reaction, adding dopamine hydrochloride, adjusting the pH to 8 and stirring to obtain polar semi-coated nanoparticles; S3, adding 3,3,3-trifluoropropyltriethoxysilane to the polar semi-coating nanoparticle dispersion and stirring, and adding octadecyltrichlorosilane to react to obtain core-shell nanoparticles; S4, adding acrylic acid to the 1-vinyl-3-butyl imidazole chloride dispersion, adding 2-vinylimidazole, mercaptopropionic acid and glyoxal to obtain an aqueous phase, then adding the oil phase to the aqueous phase, adding ammonium persulfate, and reacting to obtain a polyionic liquid nanomaterial; S5, adding the core-shell nanoparticles into an aqueous polyurethane-acrylic emulsion, and then adding polyionic liquid nanomaterials, dipropylene glycol methyl ether and a photoinitiator to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

[0006] Specifically, the method for preparing the nanomaterial coating for preventing fabric surface fuzzing comprises: S1, dispersing a cage-type polysilsesquioxane in anhydrous ethanol to obtain a cage-type polysilsesquioxane dispersion, adding the cage-type polysilsesquioxane dispersion to a graphene quantum dot dispersion, adding ammonium persulfate after ultrasonic dispersion, adjusting the temperature to a first temperature for reaction, washing and drying after the reaction to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, mixing evenly, adding ammonia water to adjust the pH to 9, adjusting the temperature to a second temperature for reaction, adding dopamine hydrochloride, adjusting the pH to 8 with ammonia water, adjusting the temperature to a third temperature for stirring, and washing by centrifugation to obtain polar semi-coated nanoparticles; S3, adding 3,3,3-trifluoropropyltriethoxysilane to the polar semi-coating nanoparticle dispersion, adjusting the temperature to the fourth temperature and stirring, then adding octadecyltrichlorosilane to continue the reaction, centrifugally washing, and vacuum drying to obtain core-shell nanoparticles; S4, adding acrylic acid, 2-vinylimidazole, mercaptopropionic acid and glyoxal to the 1-vinyl-3-butylimidazole chloride dispersion, mixing evenly to obtain an aqueous phase, then adding the oil phase to the aqueous phase, adding ammonium persulfate after ultrasonication, adjusting the temperature to a first temperature for reaction, and washing after the reaction to obtain a polyionic liquid nanomaterial; S5, adding core-shell nanoparticles into aqueous polyurethane-acrylic emulsion, stirring evenly, then adding polyionic liquid nanomaterials, mixing evenly, adding dipropylene glycol methyl ether and photoinitiator, mixing evenly, and vacuum defoaming to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

[0007] Cage polysilsesquioxane is an organic-inorganic hybrid compound with special structure and function. Its molecular structure is composed of a series of highly regular cage-like Si-O-Si skeletons. Cage polysilsesquioxane molecules have both inorganic and organic characteristics in chemical structure. The Si-O-Si skeleton provides high strength, high stability and excellent heat resistance. The surface of cage polysilsesquioxane molecules usually carries multiple active silanol groups or other types of organic groups. The silanol groups can react chemically with molecules or materials with hydroxyl, carboxyl or amine groups through covalent bonds, thereby achieving highly stable bonding, while the organic groups modified on its surface can form a stable composite structure with the target material through non-covalent interactions. Since the Si-O-Si skeleton structure of cage polysilsesquioxane has high hydrophobicity, its dispersibility in polar solvents (such as anhydrous ethanol and water) is usually poor. In order to improve the dispersibility of cage polysilsesquioxane in polar solvents, ultrasonic dispersion is adopted to promote its uniform distribution in the solvent, improve the reaction efficiency and the performance of the composite material. Graphene quantum dots are a type of graphene-derived material with a size in the range of a few nanometers. The surface of graphene quantum dots usually carries abundant oxidized groups (such as carboxyl, hydroxyl, and epoxy). These groups not only give them extremely high polarity and hydrophilicity, but also provide a variety of possibilities for their application in chemical modification and composite materials. Especially in polar solvents (such as water and ethanol), graphene quantum dots can form stable interactions with solvent molecules through electrostatic and hydrogen bonding due to the presence of surface oxidized groups, thereby achieving good dispersibility. In the preparation of functionalized polysiloxane cores, the surface active groups of graphene quantum dots (such as hydroxyl and carboxyl) can form a preliminary physical adsorption system with the silanol groups on the surface of cage-type polysilsesquioxane through hydrogen bonding or electrostatic interaction. This preliminary binding mechanism lays the foundation for subsequent chemical bonding and cross-linking reactions. In addition, the hydrophobic organic groups on the surface of cage-type polysilsesquioxane can also interact non-covalently with the aromatic rings on the surface of graphene quantum dots through π-π interactions, thereby further stabilizing the composite system of the two. The synergistic effect of this physical-chemical interaction improves the bonding strength between cage-type polysilsesquioxane and graphene quantum dots, providing structural stability for the preparation of functionalized composite materials.

[0008] In order to further realize the chemical bond connection between the cage-type polysilsesquioxane and the graphene quantum dots, ammonium persulfate is introduced as a free radical initiator in the present invention, which can decompose to generate highly active sulfate radicals, which have high oxidation ability and can react with a variety of oxygen-containing groups. The generated sulfate radicals can react with the hydroxyl or carboxyl groups on the surface of the graphene quantum dots to generate more active free radical intermediates, which can further react with the silanol groups on the surface of the cage-type polysilsesquioxane to form stable covalent bonds, thereby chemically grafting the graphene quantum dots to the surface of the cage-type polysilsesquioxane. Through this chemical bonding, the bonding strength between the graphene quantum dots and the cage-type polysilsesquioxane is enhanced, forming a functionalized polysiloxane core with high stability. In addition, the silanol groups on the surface of caged polysilsesquioxane can also generate siloxy radicals under the action of free radicals. These free radicals have high chemical activity and can further trigger condensation reactions. Two siloxy radicals can form siloxy-silicon bonds through condensation, thereby realizing the cross-linking of caged polysilsesquioxane molecules. The free radical generation on the surface of caged polysilsesquioxane and graphene quantum dots not only promotes the bonding between the two, but also triggers a cross-linking reaction, forming a three-dimensional network structure with chemical bond connections. This cross-linked network improves the chemical stability and mechanical strength of the functionalized polysiloxane core.

[0009] The molecular structure of tetraethoxysilane consists of a central silicon atom and four ethoxy groups. In an alkaline environment, the ethoxy groups in the tetraethoxysilane molecule first undergo a hydrolysis reaction under the action of water molecules to generate silanol groups and ethanol. Under alkaline conditions, the hydroxide ions provided by ammonia water can catalyze the hydrolysis reaction, making the ethoxy groups more easily replaced by the hydroxyl groups in the water molecules, thereby accelerating the generation of silanol groups. With the generation of silanol groups, condensation reactions will occur between adjacent silanol molecules to form stable silicon-oxygen-silicon bonds. Through hydrolysis and condensation reactions, tetraethoxysilane gradually forms a three-dimensional silicon-oxygen network. This network has a highly cross-linked structure and exhibits excellent chemical stability and mechanical strength. This silicon-oxygen network is not evenly distributed throughout the solution, but is preferentially deposited on the surface of the functionalized polysiloxane core. This is because the surface of the functionalized polysiloxane core has a large number of active groups (such as the silanol groups on the surface of cage-type polysilsesquioxane and the carboxyl and hydroxyl groups on the surface of graphene quantum dots). These active groups can chemically bond with the silanol groups generated by the hydrolysis of tetraethoxysilane through polycondensation, so that the silicon-oxygen network is evenly deposited on the surface of the core, forming a dense silicon-oxygen layer. After the sol-gel reaction of tetraethoxysilane is completed, dopamine hydrochloride is added and the pH of the solution is adjusted to alkaline with ammonia water. Under this condition, the dopamine molecules undergo an oxidative self-polymerization reaction, thereby forming a layer of polydopamine coating on the surface of the nanoparticles. The dopamine molecular structure contains a catechol group and a primary amine group. Under alkaline conditions, the catechol structure is first oxidized to a quinone structure. The resulting quinone structure has high chemical activity and can react with unoxidized dopamine molecules through two main pathways to form a highly cross-linked polymer network: (1) The quinone structure acts as an electrophilic reagent and undergoes a nucleophilic addition reaction with the hydroxyl group in the catechol or the nitrogen atom in the primary amine to generate a cross-linked intermediate; (2) The quinone structure can form a free radical intermediate, and polymerization occurs between the free radicals to further construct a cross-linked network. A polydopamine coating with a highly cross-linked structure is generated. During the oxidative self-polymerization of dopamine, a large number of active groups on the surface of the functionalized polysiloxane core (such as the silanol group in the silicon oxide layer, the carboxyl group and the hydroxyl group on the graphene quantum dot) can chemically combine with or physically adsorb to the polydopamine coating, so that the polydopamine coating is preferentially deposited on the surface of the core. The surface of the polydopamine coating contains a large number of polar groups (such as phenolic hydroxyl groups and amine groups), which can interact with polar solvents or polar substrates (such as fibers and fabrics) in the environment, thereby significantly improving the dispersion and compatibility of the particles; the polydopamine coating has a strong adhesion ability, allowing the nanoparticles to firmly adhere to the surface of the substrate to form a stable interface. At the same time, the phenolic hydroxyl groups and amine groups on the surface of the polydopamine coating provide rich chemically active sites for subsequent functional modifications.

[0010] The polydopamine coating on the surface of polar semi-coated nanoparticles is formed by chemical oxidation self-polymerization reaction and contains a large number of polar functional groups on its surface, such as phenolic hydroxyl and amine groups. The introduction of these polar functional groups gives the nanoparticles excellent polarity and hydrophilicity, allowing the particles to interact strongly with polar substrates (such as water, ethanol or polar fibers), thereby showing good dispersibility and stability in polar environments. This polar property makes polar semi-coated nanoparticles widely applicable in many applications, such as dispersion systems for polar solvents or modification of polar substrates. However, excessive surface polarity will limit the performance of particles in certain special environments. In aqueous phases or high humidity environments, nanoparticles may agglomerate due to hydrogen bonds or electrostatic interactions between surface polar groups, thereby reducing their dispersibility and functionality. In order to overcome this problem, further surface hydrophobic treatment of the particles becomes a key step. Hydrophobic functional groups are introduced to the surface of particles through chemical modification to significantly reduce their surface free energy and enhance hydrophobicity and oleophobicity.

[0011] The trifluoropropyltriethoxysilane molecule contains trifluoromethyl and three ethoxy groups. The trifluoromethyl group exhibits extremely low surface energy due to its unique electronegativity and non-polar properties, which can significantly improve the hydrophobicity of the particles; the ethoxy group has high chemical reactivity and can undergo hydrolysis in water or alcohol solution to generate silanol groups, thereby chemically reacting with polar functional groups on the surface of the particles. On the other hand, the octadecyltrichlorosilane molecule contains a long-chain alkyl group and three chloro groups. The long-chain alkyl group can form a stable hydrophobic layer on the surface of the particles due to its hydrophobicity, and further enhance the stability of the modified layer through the van der Waals interaction between molecules; the chloro group can undergo chemical reaction under the action of water to generate silanol groups, thereby combining with the active groups on the particle surface. In the chemical reaction of the silane coupling agent, the ethoxy or chloro group reacts with water to generate silanol groups. The generated silanol groups have high chemical activity and can combine with the polar groups rich in the surface of the particles through further chemical reactions. The surface of the polar semi-coated nanoparticles contains a polydopamine coating and a silicon oxide network. These two parts provide abundant polar groups. The silanol groups in the silane coupling agent can react chemically with the hydroxyl or amine groups on the surface of the particles to form stable chemical bonds. The trifluoromethyl groups in trifluoropropyltriethoxysilane and the long-chain alkyl groups in octadecyltrichlorosilane are bonded to the particle surface through chemical bonds. These hydrophobic groups evenly cover the surface of the particles to form a hydrophobic shell. This shell can not only significantly reduce the surface free energy of the particles, but also effectively prevent the adsorption of water or other polar molecules through the repulsive effect of the hydrophobic groups. This chemical modification significantly enhances the hydrophobicity of the particles, allowing them to maintain excellent hydrophobic properties when in contact with water or polar liquids.

[0012] The trifluoromethyl group introduced on the surface significantly reduces the hydrophilicity of the particles due to its low surface energy, making the particles highly hydrophobic in water and other polar environments. Secondly, the long-chain alkyl further improves the surface hydrophobicity through the intermolecular van der Waals force and enhances the mechanical stability of the modified layer to a certain extent. In addition, the hydrophobic treatment also greatly reduces the surface energy of the particles, reducing the adsorption tendency between particles and between particles and other substrates, thereby effectively preventing the particles from agglomerating due to the interaction of surface polar groups in high humidity or aqueous environments. The hydrophobicized nanoparticles have higher chemical stability. This is because the chemical bonds formed during the hydrophobic treatment, such as silicon-oxygen-silicon bonds and silicon-nitrogen bonds, have higher bond energy and can maintain structural integrity in acidic, alkaline or other chemical environments. This chemical stability enables the particles to be used in extreme environments, such as in highly corrosive solutions or high temperature and high humidity environments. In addition, the hydrophobic shell can also provide a physical barrier to a certain extent to prevent the functional layer inside the particle from being eroded by external chemicals, thereby extending the service life of the particles. The hydrophobic nanoparticles also show good environmental adaptability, which is mainly reflected in the significant improvement of the dispersibility and functional stability of the particles in high humidity or aqueous environments. The introduction of the hydrophobic shell reduces the polar interactions between particles, thereby effectively preventing the aggregation of particles in the aqueous phase. In addition, the hydrophobic shell can also provide additional interface protection for the particles, thereby avoiding the degradation or inactivation of the polar functional groups on the particle surface.

[0013] In the present invention, a polyionic liquid nanomaterial is prepared by combining an aqueous phase composed of 1-vinyl-3-butyl imidazole chloride, acrylic acid, 2-vinyl imidazole, mercaptopropionic acid and glyoxal, with the introduction of an oil phase and ultrasonic treatment, and a multifunctional polymer network is formed through free radical polymerization and crosslinking reaction. This polymer network forms a dense functional coating on the surface of the fabric, thereby significantly improving the anti-pilling performance of the fabric. In the prepared aqueous phase, 1-vinyl-3-butyl imidazole chloride, acrylic acid, 2-vinyl imidazole, mercaptopropionic acid and glyoxal together constitute a reaction system. These chemical components act synergistically in the subsequent free radical polymerization and crosslinking reactions to form a highly crosslinked, stable and functionalized polymer network. 1-vinyl-3-butyl imidazole chloride is an ionic liquid monomer, and the vinyl group in its molecular structure can participate in the free radical polymerization reaction and form a polymer main chain together with other monomers, and the imidazole cation provides a high polarity and chemical stability for the final material. This polar property is manifested in the anti-pilling process as the material can combine with polar groups (such as hydroxyl, amide, etc.) on the surface of fabric fibers through electrostatic action or hydrogen bonding, which helps to form a dense and stable functional coating on the fiber surface. The coating formed by chemical bonding can reduce the roughness and friction coefficient of the fiber surface, making it difficult for the fiber to be pulled out or broken when rubbed. The process of pulling the fiber out of the fabric surface is the initial stage of pilling, so this effect significantly reduces the occurrence of pilling. In addition, the imidazole cation can also enhance the adhesion of the coating to the fiber surface, ensuring that the coating is not easy to fall off during long-term use, thereby achieving the durability of the anti-pilling performance. The introduction of acrylic acid provides carboxyl function to the polymer network. The carboxyl group is a strong polar group that can combine with the polar groups on the fiber surface through hydrogen bonding. This chemical action further enhances the adhesion of the functional coating on the fiber surface, thereby improving the stability and durability of the coating. In addition, the polarity of the carboxyl group can also reduce the interaction between fibers, especially the electrostatic attraction and van der Waals force, thereby reducing the tendency of entanglement between the fiber ends. Fiber entanglement is a key step in the formation of pilling, so the addition of carboxyl groups is of great significance in anti-pilling performance.

[0014] 2-vinylimidazole is a bifunctional monomer that contains both vinyl groups to participate in polymerization reactions and functional imidazole groups. The imidazole group has a certain alkalinity. Through the interaction with the carboxyl group of acrylic acid, a complex hydrogen bond network can be formed in the coating. This hydrogen bond network provides flexibility and buffering capacity for the functional coating of the material, enabling it to absorb part of the mechanical energy during friction, thereby reducing the mechanical damage to the fiber. In addition, the imidazole group can also reduce the electrostatic attraction between the fiber ends by regulating the surface charge distribution. This electrostatic shielding effect significantly reduces the possibility of fiber entanglement, thereby inhibiting the formation of hair balls. The addition of mercaptopropionic acid and glyoxal generates thiol ether bonds through chemical reactions. This high-strength chemical bond introduces chemical crosslinking points into the polymer network. These crosslinking points form a stable three-dimensional polymer network, which significantly improves the mechanical strength and wear resistance of the material. In the process of anti-pilling, this cross-linked network plays a role through the following two mechanisms: (1) improving the mechanical properties of the coating. The cross-linked network enhances the strength and durability of the coating, making the coating less likely to be damaged or fall off during long-term friction, thereby providing continuous protection for the fiber; (2) buffering effect. The elastic properties of the cross-linked network can absorb the mechanical energy generated during friction and evenly disperse it on the fiber surface, thereby reducing the destructive effect of local stress concentration on the fiber. This effect effectively prevents the fiber from being broken or loosened. After the aqueous phase is prepared, a stable water-oil emulsion system is formed by adding the oil phase to the aqueous phase and performing ultrasonic treatment. The formation of the emulsion enables the functional material to form a more uniform coating on the fiber surface. Stress concentration on the fabric surface is one of the main reasons for fiber breakage. A uniform coating can reduce stress concentration on the fiber surface, thereby reducing the possibility of fiber breakage; at the same time, a uniformly distributed coating can adhere more firmly to the fabric surface, ensuring that the coating is not easy to fall off during long-term use; by reducing the roughness of the fiber surface, the uniform coating significantly reduces the friction coefficient between fibers, thereby reducing the generation and entanglement of broken fibers. By adding ammonium persulfate to initiate free radical polymerization, 1-vinyl-3-butyl imidazole chloride, acrylic acid and 2-vinylimidazole vinyl groups undergo ring-opening polymerization to form functional polymer chains, while mercaptopropionic acid and glyoxal further react to generate crosslinking points, building a stable three-dimensional polymer network. The introduction of the crosslinking network significantly improves the mechanical properties of the coating, allowing it to protect the fiber from being broken or falling off during friction; the carboxyl and imidazole groups on the polymer chain increase the polarity of the coating, allowing it to firmly adhere to the fiber surface through hydrogen bonds or electrostatic effects.

[0015] Waterborne polyurethane-acrylic emulsion is a polymer emulsion system with a two-phase structure, which is composed of flexible polyurethane segments and rigid acrylic segments. Its two-phase characteristics provide excellent flexibility and mechanical properties for the final coating, thereby ensuring that the coating has good adhesion, durability and wear resistance on the fabric surface. The polyurethane segment is a polymer flexible material with a large number of urethane bonds and flexible ether bonds in its molecular chain. These chemical bonds give the material good flexibility and elasticity, allowing the final coating to adapt to various bending and deformation of the fabric surface without cracking or peeling. This flexibility is particularly important for anti-pilling coatings, because the fabric will be repeatedly rubbed and stretched during use, and the coating must be able to remain intact with the deformation of the fiber surface. The acrylic segment is a rigid polymer with a highly polar carboxyl or ester group in its molecular structure, which can be combined with the fabric surface through hydrogen bonding or electrostatic interaction. This strong polar bonding significantly improves the adhesion of the coating. At the same time, the rigidity of the acrylic segment enhances the mechanical properties and wear resistance of the coating, ensuring that the coating can resist mechanical damage during long-term use. The biphasic properties of waterborne polyurethane-acrylic emulsions enable them to act as a matrix material in coatings, providing a balance of flexibility and rigidity, and providing a stable dispersion system and a basis for synergy for other functional components. The core characteristic of core-shell nanoparticles lies in their bifunctional structure, namely the synergy of polarity and hydrophobicity. The polar core of core-shell nanoparticles is composed of hydrophilic or polar materials. Polar groups can bind to polar groups (such as hydroxyl or amino groups) on the surface of fabric fibers through intermolecular forces (such as hydrogen bonds or electrostatic effects), so that core-shell nanoparticles can be firmly adsorbed on the surface of fabrics to form a stable interface layer. The polar core significantly improves the adhesion between the coating and the fiber surface through chemical bonding with the surface groups of the fabric, thereby reducing the shedding of the coating under friction or mechanical action; and the polar core homogenizes the polarity distribution on the fiber surface by covering the fabric surface, thereby reducing the mutual attraction and entanglement between fibers caused by static electricity accumulation. Fabrics are often subjected to mechanical friction during use. Hydrophobic groups reduce the damage to the fiber surface caused by mechanical friction by reducing the friction coefficient. In addition, hydrophobic groups can significantly reduce the accumulation of static electricity on the fabric surface and particle surface, thereby reducing the fiber entanglement and fuzzing caused by static electricity. The high polarity of polyionic liquid materials comes from polar groups such as imidazolium cations and carboxyl groups in their molecular structure. These polar groups can interact with polar groups (such as hydroxyl groups, amide groups, etc.) on the surface of fabric fibers to form a dense protective layer with strong interactions. The protective layer can not only reduce the roughness of the fiber surface, but also significantly reduce the friction coefficient between fibers, thereby reducing the occurrence of fuzzing. The ionic properties of polyionic liquid materials enable them to conduct electricity effectively, reduce the accumulation of static electricity on the fabric surface, and thus prevent fiber adsorption and entanglement caused by static electricity.In addition, polyionic liquid materials have a certain degree of flexibility and can play a lubricating role during the friction process, further reducing mechanical damage. The synergistic effect of core-shell nanoparticles and polyionic liquid materials is reflected in: (1) The polar core of the core-shell nanoparticles interacts with the high polarity of the polyionic liquid material, which jointly enhances the interfacial bonding force between the coating and the surface of the fabric fiber. The stability and wear resistance of the coating are thus further improved; (2) The hydrophobic shell of the core-shell nanoparticles reduces the friction coefficient between the fiber and the coating, while the polyionic liquid material further reduces friction damage through its lubricating effect. This dual effect significantly reduces the mechanical damage to the fiber surface, thereby reducing the occurrence of fuzzing; (3) The hydrophobic shell of the core-shell nanoparticles reduces static electricity accumulation, while the polyionic liquid material further enhances the antistatic performance through its ionic conductivity. This superposition effect effectively inhibits the fiber entanglement and fuzzing caused by static electricity.

[0016] As a preferred technical solution of the present invention, in S1, the mass fraction of the cage-type polysilsesquioxane dispersion is 10-15wt.%, for example, it can be 10.0wt.%, 10.5wt.%, 11.0wt.%, 11.5wt.%, 12.0wt.%, 12.5wt.%, 13.0wt.%, 13.5wt.%, 14.0wt.%, 14.5wt.% or 15.0wt.%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are equally applicable.

[0017] In some optional embodiments, the ultrasonic dispersion time is 30-40 min, for example, it can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] In some optional embodiments, the mass ratio of the cage-type polysilsesquioxane to the graphene quantum dots is 1:(0.05-0.1), for example, it can be 1:0.05, 1:0.055, 1:0.06, 1:0.065, 1:0.07, 1:0.075, 1:0.08, 1:0.085, 1:0.09, 1:0.095 or 1:0.1, but is not limited to the listed ratios, and other unlisted values ​​within the ratio range are also applicable.

[0019] In some optional embodiments, the solvent of the graphene quantum dot dispersion is ethanol-water solution, and the volume ratio of anhydrous ethanol to deionized water is 1:2.

[0020] In some optional embodiments, the mass of the ammonium persulfate is 1-2% of the mass of the cage-type polysilsesquioxane, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0021] In some optional embodiments, the first temperature is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed temperatures, and other unlisted temperatures within the temperature range are also applicable.

[0022] In some optional embodiments, the first temperature reaction time is 4-6h, for example, it can be 4.0h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed times, and other unlisted times within the time range are also applicable.

[0023] In some optional embodiments, the drying temperature is 70-80°C, for example, it can be 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed temperatures, and other unlisted temperatures within the temperature range are also applicable.

[0024] In some optional embodiments, the drying time is 10-12 hours, for example, it can be 10.0h, 10.2h, 10.4h, 10.6h, 10.8h, 11.0h, 11.2h, 11.4h, 11.6h, 11.8h or 12.0h, but is not limited to the listed times, and other unlisted times within the time range are also applicable.

[0025] As a preferred technical solution of the present invention, in S2, the mass ratio of the functionalized polysiloxane core to tetraethoxysilane is 1:(0.5-1), for example, it can be 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95 or 1:1, but is not limited to the listed ratios, and other unlisted values ​​within the ratio range are also applicable.

[0026] In some optional embodiments, the solvent of the tetraethoxysilane dispersion is an ethanol aqueous solution, and the volume ratio of deionized water to anhydrous ethanol is 1:1.

[0027] In some optional embodiments, the second temperature is 40-50°C, for example, it can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed temperatures, and other unlisted temperatures within the temperature range are also applicable.

[0028] In some optional embodiments, the second temperature reaction time is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed times, and other unlisted times within the time range are also applicable.

[0029] In some optional embodiments, the mass of the dopamine hydrochloride is 10-20% of the mass of the functionalized polysiloxane core, for example, it can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0030] In some optional embodiments, the third temperature is 25-30°C, for example, it can be 25°C, 25.5°C, 26°C, 26.5°C, 27°C, 27.5°C, 28°C, 28.5°C, 29°C, 29.5°C or 30°C, but is not limited to the listed temperatures, and other unlisted temperatures within the temperature range are also applicable.

[0031] In some optional embodiments, the stirring time at the third temperature is 3-4h, for example, it can be 3.0h, 3.1h, 3.2h, 3.3h, 3.4h, 3.5h, 3.6h, 3.7h, 3.8h, 3.9h or 4.0h, but is not limited to the listed times, and other unlisted times within the time range are also applicable.

[0032] As a preferred technical solution of the present invention, in S3, the mass fraction of the polar semi-coating nanoparticle dispersion is 1-2wt.%, for example, it can be 1.0wt.%, 1.1wt.%, 1.2wt.%, 1.3wt.%, 1.4wt.%, 1.5wt.%, 1.6wt.%, 1.7wt.%, 1.8wt.%, 1.9wt.% or 2.0wt.%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0033] In some optional embodiments, the mass of the 3,3,3-trifluoropropyltriethoxysilane is 3-5% of the mass of the polar semi-coating nanoparticles, for example, it can be 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.6%, 4.8% or 5.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0034] In some optional embodiments, the fourth temperature is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed temperatures, and other unlisted temperatures within the temperature range are also applicable.

[0035] In some optional embodiments, the stirring time at the fourth temperature is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed times, and other unlisted times within the time range are also applicable.

[0036] In some optional embodiments, the mass of the octadecyltrichlorosilane is 1-2% of the mass of the polar semi-coating nanoparticles, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0037] In some optional embodiments, the time for continuing the reaction after adding octadecyltrichlorosilane is 2-3h, for example, it can be 2.0h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h or 3.0h, but is not limited to the listed times, and other times not listed within the time range are also applicable.

[0038] As a preferred technical solution of the present invention, in S4, the mass fraction of the 1-vinyl-3-butylimidazole chloride dispersion is 10-15wt.%, for example, it can be 10.0wt.%, 10.5wt.%, 11.0wt.%, 11.5wt.%, 12.0wt.%, 12.5wt.%, 13.0wt.%, 13.5wt.%, 14.0wt.%, 14.5wt.% or 15.0wt.%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are equally applicable.

[0039] In some optional embodiments, the mass ratio of the 1-vinyl-3-butyl imidazole chloride to acrylic acid is 7:3.

[0040] In some optional embodiments, the mass of the 2-vinylimidazole is 1-2% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0041] In some optional embodiments, the mass of the mercaptopropionic acid is 3-4% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, for example, it can be 3.0%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9% or 4.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0042] In some optional embodiments, the molar ratio of mercaptopropionic acid to glyoxal is 1.5:1.

[0043] In some optional embodiments, the volume ratio of the water phase to the oil phase is 9:1.

[0044] In some optional embodiments, the oil phase is a sodium dodecyl sulfate dispersion having a mass fraction of 5-7wt.%, for example, 5.0wt.%, 5.2wt.%, 5.4wt.%, 5.6wt.%, 5.8wt.%, 6.0wt.%, 6.2wt.%, 6.4wt.%, 6.6wt.%, 6.8wt.% or 7.0wt.%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are equally applicable.

[0045] In some optional embodiments, the ultrasound time is 10-15 min, for example, it can be 10.0 min, 10.5 min, 11.0 min, 11.5 min, 12.0 min, 12.5 min, 13.0 min, 13.5 min, 14.0 min, 14.5 min or 15.0 min, but is not limited to the listed times, and other unlisted times within the time range are also applicable.

[0046] In some optional embodiments, the mass of the ammonium persulfate is 0.5-1% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, for example, it can be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0047] As a preferred technical solution of the present invention, in S5, the solid content of the aqueous polyurethane-acrylic emulsion is 30wt.%, and the volume ratio of the aqueous polyurethane emulsion to the acrylic emulsion is 1:1.

[0048] In some optional embodiments, the mass of the core-shell nanoparticles is 4-5% of the total mass of the aqueous polyurethane and acrylic acid, for example, it can be 4.0%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9% or 5.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0049] In some optional embodiments, the mass of the polyionic liquid nanomaterial is 2-3% of the total mass of the aqueous polyurethane and acrylic acid, for example, it can be 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9% or 3.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0050] In some optional embodiments, the mass of the dipropylene glycol methyl ether is 1-2% of the total mass of the waterborne polyurethane and acrylic acid, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0051] In some optional embodiments, the photoinitiator is benzophenone, and the mass of benzophenone is 0.5-1% of the total mass of the waterborne polyurethane and acrylic acid, for example, it can be 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95% or 1.0%, but is not limited to the listed percentages, and other unlisted values ​​within the percentage range are also applicable.

[0052] In a second aspect, the present invention provides a nano-material coating for resisting fabric surface fuzzing prepared by the method for preparing a nano-material coating for resisting fabric surface fuzzing described in the first aspect.

[0053] Compared with the prior art, the present invention has the following beneficial effects: (1) the coating performance is improved through the synergistic effect of core-shell nanoparticles, polyionic liquid materials and aqueous polyurethane-acrylic emulsions. The polar groups of the core-shell nanoparticles are tightly combined with the polar groups on the fiber surface, thereby enhancing the adhesion of the coating. At the same time, the hydrophobic groups reduce the friction coefficient and static electricity accumulation. The polyionic liquid materials provide dual protection of antistatic and anti-friction, while the aqueous polyurethane-acrylic emulsion ensures the flexibility and mechanical strength of the coating. (2) The addition of mercaptopropionic acid and glyoxal generates thiol ether bonds through chemical reactions. This high-strength chemical bond introduces chemical crosslinking points into the polymer network, forming a stable three-dimensional polymer network, thereby enhancing the strength and durability of the coating, making the coating less likely to be damaged or fall off during long-term friction. The elastic properties of the crosslinked network can absorb the mechanical energy generated during the friction process and evenly disperse it on the fiber surface, thereby reducing the destructive effect of local stress concentration on the fiber and preventing the fiber from being broken or loosened. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a SEM image of the polyionic liquid nanomaterial provided in Example 1 of the present invention (scale: 2 μm); Figure 2 This is a SEM image of the polyionic liquid nanomaterial provided in Example 1 of the present invention (scale: 1 μm). DETAILED DESCRIPTION

[0055] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0056] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products without any further purification treatment.

[0057] Example 1

[0058] This embodiment provides a nano-material coating for preventing fuzzing on the surface of fabrics, and the preparation method thereof specifically comprises the following steps: S1, dispersing cage-type polysilsesquioxane in anhydrous ethanol to obtain a cage-type polysilsesquioxane dispersion with a mass fraction of 11wt.%, adding the cage-type polysilsesquioxane dispersion to a graphene quantum dot dispersion, wherein the mass ratio of cage-type polysilsesquioxane to graphene quantum dots is 1:0.05, after ultrasonic dispersion for 33 minutes, adding ammonium persulfate with a mass of 1.2% of the mass of cage-type polysilsesquioxane, adjusting the temperature to 66°C to react for 4.2 hours, washing after the reaction and drying at 77°C for 10.2 hours to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, wherein the mass ratio of the functionalized polysiloxane core to the tetraethoxysilane is 1:0.5, and after mixing evenly, adding ammonia water to adjust the pH to 9, adjusting the temperature to 44°C and reacting for 2.4 hours, then adding dopamine hydrochloride with a mass of 11% of the mass of the functionalized polysiloxane core, adjusting the pH to 8 with ammonia water, adjusting the temperature to 25°C and stirring for 3.2 hours, and obtaining polar semi-coated nanoparticles after centrifugation and washing; S3, adding 3,3,3-trifluoropropyltriethoxysilane in an amount of 3.2% by mass of the polar semi-coating nanoparticles to a dispersion of polar semi-coating nanoparticles in an amount of 1.4 wt.%, adjusting the temperature to 55°C and stirring for 2.3 h, then adding octadecyltrichlorosilane in an amount of 1.7% by mass of the polar semi-coating nanoparticles and continuing the reaction for 2.8 h, centrifuging, washing, and vacuum drying to obtain core-shell nanoparticles; S4, adding acrylic acid to a 11wt.% 1-vinyl-3-butylimidazole chloride dispersion, the mass ratio of 1-vinyl-3-butylimidazole chloride to acrylic acid being 7:3, adding 2-vinylimidazole with a mass of 1.2% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, and mercaptopropionic acid and glyoxal with a mass of 3.3% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, the molar ratio of mercaptopropionic acid to glyoxal being 1.5:1, mixing evenly to obtain an aqueous phase, and then adding an oil phase to the aqueous phase, the volume ratio of the aqueous phase to the oil phase being 9:1, the oil phase being a 5.2wt.% sodium dodecylsulfonate dispersion, adding ammonium persulfate with a mass of 0.5% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid after ultrasonication for 12 minutes, adjusting the temperature to 66°C for reaction for 4.1 hours, and washing after the reaction to obtain a polyionic liquid nanomaterial; S5, adding core-shell nanoparticles to an aqueous polyurethane-acrylic emulsion with a solid content of 30wt.%, wherein the mass of the core-shell nanoparticles is 4.2% of the total mass of the aqueous polyurethane and the acrylic acid, stirring evenly, adding a polyionic liquid nanomaterial with a mass of 2.8% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, adding dipropylene glycol methyl ether with a mass of 1.5% of the total mass of the aqueous polyurethane and the acrylic acid and benzophenone with a mass of 0.5% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, and vacuum defoaming to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

[0059] Figure 1 SEM image (2 μm) of the polyionic liquid nanomaterial provided in this embodiment; Figure 2 The SEM image (1 μm) of the polyionic liquid nanomaterial provided in this embodiment clearly shows the three-dimensional polymer network structure of the material, which can improve the mechanical properties of the coating and enhance the strength and durability of the coating.

[0060] Example 2

[0061] This embodiment provides a nano-material coating for preventing fuzzing on the surface of fabrics, and the preparation method thereof specifically comprises the following steps: S1, dispersing a cage-type polysilsesquioxane in anhydrous ethanol to obtain a cage-type polysilsesquioxane dispersion with a mass fraction of 13wt.%, adding the cage-type polysilsesquioxane dispersion to a graphene quantum dot dispersion, wherein the mass ratio of the cage-type polysilsesquioxane to the graphene quantum dots is 1:0.1, after ultrasonic dispersion for 38 minutes, adding ammonium persulfate with a mass of 1.7% of the mass of the cage-type polysilsesquioxane, adjusting the temperature to 61°C to react for 4.9 hours, washing after the reaction and drying at 71°C for 11.7 hours to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, wherein the mass ratio of the functionalized polysiloxane core to the tetraethoxysilane is 1:0.9, and after uniform mixing, adding ammonia water to adjust the pH to 9, adjusting the temperature to 41°C and reacting for 2.1 hours, then adding dopamine hydrochloride with a mass of 17% of the mass of the functionalized polysiloxane core, adjusting the pH to 8 with ammonia water, adjusting the temperature to 29°C and stirring for 3.6 hours, and obtaining polar semi-coated nanoparticles after centrifugation and washing; S3, adding 3,3,3-trifluoropropyltriethoxysilane in an amount of 4.8% by mass of the polar semi-coating nanoparticles to a dispersion of polar semi-coating nanoparticles in an amount of 1.3 wt.%, adjusting the temperature to 51°C and stirring for 2.8 h, then adding octadecyltrichlorosilane in an amount of 1.9% by mass of the polar semi-coating nanoparticles and continuing the reaction for 2.1 h, centrifuging and washing, and vacuum drying to obtain core-shell nanoparticles; S4, adding acrylic acid to a 14wt.% 1-vinyl-3-butylimidazole chloride dispersion, the mass ratio of 1-vinyl-3-butylimidazole chloride to acrylic acid being 7:3, adding 2-vinylimidazole with a mass of 1.8% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, and mercaptopropionic acid and glyoxal with a mass of 3.9% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, the molar ratio of mercaptopropionic acid to glyoxal being 1.5:1, mixing evenly to obtain an aqueous phase, and then adding an oil phase to the aqueous phase, the volume ratio of the aqueous phase to the oil phase being 9:1, the oil phase being a 6.7wt.% sodium dodecylsulfonate dispersion, adding ammonium persulfate with a mass of 0.8% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid after ultrasonication for 11 minutes, adjusting the temperature to 61°C for reaction for 4.7 hours, and washing after the reaction to obtain a polyionic liquid nanomaterial; S5, adding core-shell nanoparticles to an aqueous polyurethane-acrylic emulsion with a solid content of 30wt.%, wherein the mass of the core-shell nanoparticles is 4.9% of the total mass of the aqueous polyurethane and the acrylic acid, stirring evenly, adding a polyionic liquid nanomaterial with a mass of 2.1% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, adding dipropylene glycol methyl ether with a mass of 1.1% of the total mass of the aqueous polyurethane and the acrylic acid and benzophenone with a mass of 0.7% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, and vacuum defoaming to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

[0062] Example 3

[0063] This embodiment provides a nano-material coating for preventing fuzzing on the surface of fabrics, and the preparation method thereof specifically comprises the following steps: S1, dispersing cage-type polysilsesquioxane in anhydrous ethanol to obtain a cage-type polysilsesquioxane dispersion with a mass fraction of 15wt.%, adding the cage-type polysilsesquioxane dispersion to a graphene quantum dot dispersion, wherein the mass ratio of cage-type polysilsesquioxane to graphene quantum dots is 1:0.07, and after ultrasonic dispersion for 31 minutes, adding ammonium persulfate with a mass of 1.9% of the mass of the cage-type polysilsesquioxane, adjusting the temperature to 69°C to react for 4.6 hours, washing after the reaction and drying at 73°C for 11.3 hours to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, wherein the mass ratio of the functionalized polysiloxane core to the tetraethoxysilane is 1:0.6, and after uniform mixing, adding ammonia water to adjust the pH to 9, adjusting the temperature to 48°C and reacting for 2.9 hours, then adding dopamine hydrochloride with a mass of 14% of the mass of the functionalized polysiloxane core, adjusting the pH to 8 with ammonia water, adjusting the temperature to 27°C and stirring for 3.1 hours, and obtaining polar semi-coated nanoparticles after centrifugation and washing; S3, adding 3,3,3-trifluoropropyltriethoxysilane in an amount of 3.7% by mass of the polar semi-coating nanoparticles to a dispersion of polar semi-coating nanoparticles in an amount of 1.9 wt.%, adjusting the temperature to 58°C and stirring for 2.1 h, then adding octadecyltrichlorosilane in an amount of 1.2% by mass of the polar semi-coating nanoparticles and continuing the reaction for 2.7 h, centrifuging and washing, and vacuum drying to obtain core-shell nanoparticles; S4, adding acrylic acid to a 15wt.% 1-vinyl-3-butylimidazole chloride dispersion, the mass ratio of 1-vinyl-3-butylimidazole chloride to acrylic acid being 7:3, adding 2-vinylimidazole with a mass of 1.4% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, and mercaptopropionic acid and glyoxal with a mass of 3.1% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, the molar ratio of mercaptopropionic acid to glyoxal being 1.5:1, mixing evenly to obtain an aqueous phase, and then adding an oil phase to the aqueous phase, the volume ratio of the aqueous phase to the oil phase being 9:1, the oil phase being a 6.2wt.% sodium dodecylsulfonate dispersion, adding ammonium persulfate with a mass of 0.6% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid after ultrasonication for 14 minutes, adjusting the temperature to 69°C for reaction for 4.2 hours, and washing after the reaction to obtain a polyionic liquid nanomaterial; S5, adding core-shell nanoparticles to an aqueous polyurethane-acrylic emulsion with a solid content of 30wt.%, wherein the mass of the core-shell nanoparticles is 4.5% of the total mass of the aqueous polyurethane and the acrylic acid, stirring evenly, adding a polyionic liquid nanomaterial with a mass of 2.5% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, adding dipropylene glycol methyl ether with a mass of 1.4% of the total mass of the aqueous polyurethane and the acrylic acid and benzophenone with a mass of 0.6% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, and vacuum defoaming to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

[0064] Example 4

[0065] This embodiment provides a nano-material coating for preventing fuzzing on the surface of fabrics, and the preparation method thereof specifically comprises the following steps: S1, dispersing cage-type polysilsesquioxane in anhydrous ethanol to obtain a cage-type polysilsesquioxane dispersion with a mass fraction of 12wt.%, adding the cage-type polysilsesquioxane dispersion to a graphene quantum dot dispersion, wherein the mass ratio of cage-type polysilsesquioxane to graphene quantum dots is 1:0.08, after ultrasonic dispersion for 36 minutes, adding ammonium persulfate with a mass of 1.4% of the mass of cage-type polysilsesquioxane, adjusting the temperature to 63°C to react for 4.1 hours, washing after the reaction and drying at 79°C for 10.5 hours to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, wherein the mass ratio of the functionalized polysiloxane core to the tetraethoxysilane is 1:1, and after uniform mixing, adding ammonia water to adjust the pH to 9, adjusting the temperature to 46°C for reaction for 2.5 hours, and then adding dopamine hydrochloride with a mass of 18% of the mass of the functionalized polysiloxane core, adjusting the pH to 8 with ammonia water, adjusting the temperature to 26°C and stirring for 3.9 hours, and obtaining polar semi-coated nanoparticles after centrifugation and washing; S3, adding 3,3,3-trifluoropropyltriethoxysilane in an amount of 4.4% by weight of the polar semi-coating nanoparticles to a dispersion of polar semi-coating nanoparticles in an amount of 1.6 wt.%, adjusting the temperature to 52°C and stirring for 2.6 h, then adding octadecyltrichlorosilane in an amount of 1.4% by weight of the polar semi-coating nanoparticles and continuing the reaction for 2.5 h, centrifuging, washing, and vacuum drying to obtain core-shell nanoparticles; S4, adding acrylic acid to a 12wt.% 1-vinyl-3-butylimidazole chloride dispersion, the mass ratio of 1-vinyl-3-butylimidazole chloride to acrylic acid being 7:3, adding 2-vinylimidazole with a mass of 1.7% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, and mercaptopropionic acid and glyoxal with a mass of 3.7% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, the molar ratio of mercaptopropionic acid to glyoxal being 1.5:1, mixing evenly to obtain an aqueous phase, and then adding an oil phase to the aqueous phase, the volume ratio of the aqueous phase to the oil phase being 9:1, the oil phase being a 5.5wt.% sodium dodecylsulfonate dispersion, adding ammonium persulfate with a mass of 1% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid after ultrasonication for 15 minutes, adjusting the temperature to 63°C for reaction for 4.9 hours, and washing after the reaction to obtain a polyionic liquid nanomaterial; S5, adding core-shell nanoparticles to an aqueous polyurethane-acrylic emulsion with a solid content of 30wt.%, wherein the mass of the core-shell nanoparticles is 4.8% of the total mass of the aqueous polyurethane and the acrylic acid, stirring evenly, adding a polyionic liquid nanomaterial with a mass of 2.7% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, adding dipropylene glycol methyl ether with a mass of 1.9% of the total mass of the aqueous polyurethane and the acrylic acid and benzophenone with a mass of 0.9% of the total mass of the aqueous polyurethane and the acrylic acid, mixing evenly, and vacuum defoaming to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

[0066] Comparative Example 1 This comparative example provides a nanomaterial coating for preventing fuzzing on the surface of fabrics. The difference between it and Example 1 is that the mass of dopamine hydrochloride in S2 is 1% of the mass of the functionalized polysiloxane core, which is 10% less than that in Example 1. The other process parameters and operating conditions are exactly the same as those in Example 1.

[0067] Comparative Example 2 This comparative example provides a nanomaterial coating for preventing fuzzing on the surface of fabrics. The difference between it and Example 1 is that the mass of dopamine hydrochloride in S2 is 30% of the mass of the functionalized polysiloxane core, which is an increase of 19% compared with Example 1. The other process parameters and operating conditions are exactly the same as those in Example 1.

[0068] Comparative Example 3 This comparative example provides a nanomaterial coating for preventing fabric surface fuzzing. The difference between it and Example 1 is that the mass of mercaptopropionic acid in S4 is 0.3% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, which is 3% less than that in Example 1. The other process parameters and operating conditions are exactly the same as those in Example 1.

[0069] Comparative Example 4 This comparative example provides a nanomaterial coating for preventing fuzzing on the surface of fabrics. The difference between it and Example 1 is that the mass of mercaptopropionic acid in S4 is 6.3% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid, which is 3% higher than that in Example 1. The other process parameters and operating conditions are exactly the same as those in Example 1.

[0070] Fabric treatment method: soak the fabric to be treated in deionized water and neutral detergent for 10 minutes, rinse repeatedly until no residue is left, then dry at 60°C to a moisture content of ≤10%, immerse the dried fabric in a nano-material coating that resists fuzzing on the fabric surface for 3 minutes, control the liquid carrying rate to 80% with a roller pressure (0.1MPa), pre-dry at 50°C for 10 minutes, transfer to 110°C for 20 minutes, and then irradiate with ultraviolet light of wavelength 300-400nm (intensity 200mW / cm 2 ) for 5 min. The test method is GB / T4802.4-2020. The test results are shown in Table 1.

[0071] Table 1 Test results of nanomaterial coatings for preventing fuzzing on fabric surfaces in Examples 1 to 4 and Comparative Examples 1 to 4

[0072] It can be seen from Table 1 that compared with Example 1, the pilling level, fuzzing level and felting level of Comparative Example 1 are all reduced; the pilling level, fuzzing level and felting level of Comparative Example 2 are all reduced. Dopamine hydrochloride forms a dopamine coating through oxidative polymerization under weak alkaline conditions. The hydroxyl and amino groups on its surface give polarity and adsorption capacity. In Comparative Example 1, there is insufficient dopamine hydrochloride, resulting in a weak bonding force between the coating and the fiber surface. In this way, the fabric is more susceptible to friction during use, and the fiber ends gradually protrude from the fabric surface and entangle to form pilling. At the same time, the electrostatic shielding ability of the polar coating is insufficient, and the friction coefficient between the fiber surfaces is high, and the fibers are easily entangled, resulting in felting. In Comparative Example 2, there is too much dopamine hydrochloride. Excessive dopamine hydrochloride will lead to excessive deposition of polydopamine, making the coating harder and uneven, thereby increasing the shear stress on the fibers during friction, causing the fibers to break and form pilling. Excessive dopamine will cause the polydopamine coating to become thicker and lose its flexibility, and the enhanced rigidity of the fabric surface will destroy the relative sliding ability between fibers, thereby increasing friction loss and causing pilling.

[0073] As shown in Table 1, compared with Example 1, the pilling level, fuzzing level and felting level of Comparative Example 3 are all reduced; the pilling level, fuzzing level and felting level of Comparative Example 4 are all reduced. Mercaptopropionic acid is an important chemical component to realize the functionality of polyionic liquid nanomaterials. Its thiol and carboxyl groups introduce polarity and chemical activity through copolymerization with other monomers (such as 1-vinyl-3-butylimidazole chloride, acrylic acid and 2-vinylimidazole), thereby giving the nanomaterial antistatic ability. In Comparative Example 3, mercaptopropionic acid is insufficient, the polarity and electrostatic shielding ability of the polyionic liquid are reduced, the lubricity and bonding force between the coating and the fiber are weakened, and the fiber is more likely to entangle into balls during friction. In Comparative Example 4, there is an excess of mercaptopropionic acid, which may cause the coating surface to be too polarized. At the same time, the rigidity of the coating increases due to excessive cross-linking, and the fibers are more likely to break and form pilling during friction. Excessive polar groups (such as carboxyl groups) will significantly increase the hydrophilicity of the coating, increase the water adsorption on the fiber surface, make it easier for fibers to become entangled, and accelerate the felting speed, especially under wet friction conditions.

[0074] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a nanomaterial coating for preventing fuzzing on the surface of fabrics, characterized in that: The preparation method comprises: S1, adding a cage-type polysilsesquioxane dispersion into a graphene quantum dot dispersion, adding ammonium persulfate, and reacting to obtain a functionalized polysiloxane core; S2, dispersing the functionalized polysiloxane core in a tetraethoxysilane dispersion, adjusting the pH to 9 for reaction, adding dopamine hydrochloride, adjusting the pH to 8 and stirring to obtain polar semi-coated nanoparticles; S3, adding 3,3,3-trifluoropropyltriethoxysilane to the polar semi-coating nanoparticle dispersion and stirring, and adding octadecyltrichlorosilane to react to obtain core-shell nanoparticles; S4, adding acrylic acid to the 1-vinyl-3-butyl imidazole chloride dispersion, adding 2-vinylimidazole, mercaptopropionic acid and glyoxal to obtain an aqueous phase, then adding the oil phase to the aqueous phase, adding ammonium persulfate, and reacting to obtain a polyionic liquid nanomaterial; S5, adding the core-shell nanoparticles into an aqueous polyurethane-acrylic emulsion, and then adding polyionic liquid nanomaterials, dipropylene glycol methyl ether and a photoinitiator to obtain a nanomaterial coating that resists fuzzing on the fabric surface.

2. The method for preparing a nano-material coating for preventing fabric surface fuzzing according to claim 1, characterized in that: In S1: The mass fraction of the cage-type polysilsesquioxane dispersion is 10-15wt.%; The mass ratio of the cage-type polysilsesquioxane to the graphene quantum dots is 1:(0.05-0.1).

3. The method for preparing a nano-material coating for preventing fabric surface fuzzing according to claim 1, characterized in that: In S1: The mass of the ammonium persulfate is 1%-2% of the mass of the cage-type polysilsesquioxane.

4. The method for preparing a nano-material coating for preventing fabric surface fuzzing according to claim 1, characterized in that: In S2: The mass ratio of the functionalized polysiloxane core to tetraethoxysilane is 1:(0.5-1); The mass of the dopamine hydrochloride is 10%-20% of the mass of the functionalized polysiloxane core.

5. The method for preparing a nano-material coating for preventing fuzzing on the surface of fabric according to claim 1, characterized in that: In S3: The mass fraction of the polar semi-coating nanoparticle dispersion is 1-2wt.%; The mass of the 3,3,3-trifluoropropyltriethoxysilane is 3%-5% of the mass of the polar semi-coating nanoparticles.

6. The method for preparing a nano-material coating for preventing fabric surface fuzzing according to claim 1, characterized in that: In S3: The mass of the octadecyltrichlorosilane is 1%-2% of the mass of the polar semi-coating nanoparticles.

7. The method for preparing a nano-material coating for preventing fabric surface fuzzing according to claim 1, characterized in that: In S4: The mass ratio of 1-vinyl-3-butyl imidazole chloride to acrylic acid is 7:3; The mass of the 2-vinylimidazole is 1%-2% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid; The mass of the mercaptopropionic acid is 3%-4% of the total mass of 1-vinyl-3-butylimidazole chloride and acrylic acid.

8. The method for preparing a nano-material coating for preventing fabric surface fuzzing according to claim 1, characterized in that: In S5: The mass of the core-shell nanoparticles is 4%-5% of the total mass of the waterborne polyurethane and acrylic acid; The mass of the polyionic liquid nanomaterial is 2%-3% of the total mass of the waterborne polyurethane and the acrylic acid.

9. The method for preparing a nano-material coating for preventing fuzzing on the surface of fabric according to claim 1, characterized in that: In S5: The mass of the dipropylene glycol methyl ether is 1%-2% of the total mass of the waterborne polyurethane and acrylic acid; The photoinitiator is benzophenone, and the mass of benzophenone is 0.5%-1% of the total mass of the waterborne polyurethane and the acrylic acid.

10. A nanomaterial coating for resisting fuzzing on the surface of fabrics is obtained by adopting the method for preparing a nanomaterial coating for resisting fuzzing on the surface of fabrics as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation technology of soft highly-elastic fabric anti-fluffing anti-pilling finishing agent

    CN101302276A

  • Anti-pilling agent for cashmere fabric and production method

    CN107663770A

  • Preparation method of nano-silver in situ doped waterborne polyurethane textile finishing agent and product thereof

    CN108589276A

  • Cationic polyurethane modified polyacrylate emulsion with crosslinked core-shell structure and preparation method thereof

    CN109232824A

  • Anti-pilling polyester cotton knitted fabric and preparation method thereof

    CN112941924A